Ways of mastering folklore works for children - Baltymova, М.Р. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
This article describes that folklore works for children represent the noble heritage of our people accumulated over the centuries, based on the formation of preschool children’s own fantasies, claims, judgments, and opportunities to aesthetically perceive and feel the surrounding phenomenon. The generalization of the heritage of children’s folklore, the assimilation of spiritual food left to the descendants of our ancestors, the development of the history of its origin, the conduct of scientific analysis, experience indicate the results of considerable work. Folklore works for children are a valuable genre that listens to them with pleasure, increases their creative qualities, develops logical thinking and vocabulary. Almost all meaningful works written in accordance with the peculiarities of the development of child psychology contribute to the development of their cognitive abilities, increase their vocabulary, increase their thinking and speech abilities. In the works of the scientist-educator A. Baitursynov tells that fairy tales, proverbs, sayings, edifications and tales for children today are a valuable tool for educating teenagers on the principles of folk pedagogy, systematization and scientific justification of the values of cultural heritage. Folklore works as the sources of folk heritage from the day of the child’s birth occupy an important place as one of the optimal means of education, aimed directly at education. The question raised in the article does not lose its relevance and significance, is revived and modernized, increasing the knowledge and skills of the family, parents, the population, and society as a whole. Children absorbs the words of the mother, with age, the child’s soul is filled with special feelings, enriched, filled.